In-Depth Comparison of PV Array Configurations and Boost Converter Topologies Using P&O and PSO Techniques - Talha, Fatma; Khalil Benmouiza; Mouhoub Birane (Journal Europeen des Systemes Automatises, 2024)
In the search for efficient renewable energy solutions, grid-connected photovoltaic (PV) systems have become a key technology. This paper delves into optimizing these systems through a thorough comparison of various PV array and boost converter topologies, employing advanced Maximum Power Point Tracking (MPPT) algorithms. Utilizing simulations, the research scrutinizes diverse configurations of PV arrays, including series and parallel, in conjunction with different boost converter designs. The focus is on enhancing power output in different irradiation conditions. Key performance metrics, such as efficiency, tracking precision, and system stability, are rigorously evaluated. The comparative analysis primarily hinges on two MPPT techniques: the Perturb and Observe (P&O) method and the Particle Swarm Optimization (PSO) algorithm. This investigation not only provides critical insights into the optimal selection of PV array and boost converter configurations for grid-connected systems but also underscores the superiority of intelligent algorithms like PSO in enhancing operational efficacy. Results demonstrate a remarkable 99% efficiency and energy output advantage of the parallel PV array configuration compared to the series configuration.